Climate-related innovations, crowding out, and their impact on competitiveness - Hanna Hottenrott; Sascha Rexhäuser; Reinhilde Veugelers (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Within the last few decades, rising environmental concerns, particularly about global climate change, have forced policy-makers to act in an effort to mitigate further harm. Yet though greenhouse gas emissions and the wasteful use of natural resources are detrimental to the environment, policy-makers are reluctant to enact any green legislation that might undermine national competitiveness. This is the main reason why governments often fail to agree on legally binding emissions targets on the international level. Many now see the solution to lie in the development of new environmental technologies, which promise to address environmental problems while maintaining a strong economy and competitiveness. This ZEW project examines the effects of environmental technology on competitiveness, especially as it relates to the governmental regulation of pollutants. A key determinant for the proliferation of green technology - and for tackling the environmental problems they are meant to solve - is whether they produce positive returns. – – Wachsende Umweltbelange haben in den letzten Jahrzehnten den Druck auf politische Entscheidungsträger erhöht, Maßnahmen zur Verhinderung weiterer ökologischer Schäden zu ergreifen. Doch obwohl Treibhausgasemissionen und der verschwenderische Umgang mit natürlichen Ressourcen schädlich für die Umwelt sind, zögert die Politik, umweltfreundliche Gesetze zu implementieren, von denen Nachteile für die nationale Wettbewerbsfähigkeit befürchtet werden. Viele sehen daher die Lösung in der Entwicklung umweltfreundlicher Technologien, die ökologische Probleme lindern könnten, ohne die Wettbewerbsfähigkeit zu beeinträchtigen. Der Einfluss von Innovationen mit Umweltwirkung auf die Wettbewerbsfähigkeit ist Gegenstand dieser ZEW-Studie.
Keywords: 330